Environmental externality of coal use in China: Welfare effect and tax regulation. (15th October 2015) - Chen, Zhan-Ming; Liu, Yu; Qin, Ping; Zhang, Bo; Lester, Leo; Chen, Guanghua; Guo, Yumei; Zheng, Xinye
Highlights: China's interprovincial embodied CO2 flows are evaluated in monetary unit. A carbon tax complemented with VAT adjustment is proposed and analyzed. The carbon tax leads to significant wealth redistribution if not adequately offset. Resource-abundant provinces are hit harder from the carbon tax. Abstract: This study employs a multi-regional input–output model at the provincial level to evaluate the environmental costs of coal burning in China in 2007, in terms of its damages from climate change externality. According to the results, the contributions of central-west provinces to the national economy are significantly underestimated because the hidden environmental inputs are not reflected by conventional national account. For example, if the externality of CO2 emission is monetized to be 20 USD/ton (152 RMB/ton), the net external cost introduced by Shanxi in 2007 amounts to nearly 8 billion USD (59 billion RMB), which is equivalent to over one tenth of the annual local output. Our results confirm that developed regions, such as Beijing and Guangdong, shape their low-emission profiles by transferring embodied emission flows to less developed regions. By using a Pigouvian tax to correct for the environmental externality, national consumer price index, producer price index, export price, and gross domestic product deflator will increase by 2.28%, 3.94%, 1.44%, and 1.61%, respectively. To offset the inflationary effect, a complementary measure of reducing domestic value-added tax rate is proposed and analyzed.